Endovascular repair with the Gore thoracoabdominal multibranch endoprosthesis for proximal degeneration after prior fenestrated endovascular aortic repair - Lauren Cralle, MD; Kathryn DiLosa, MD, MPH; Steven Maximus, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Degeneration of the thoracoabdominal aorta proximal to a prior fenestrated endovascular aortic repair represents a complex issue with limited options for repair. Previously, modified endografts or open conversion with endograft explant offered the only options for management. Here we describe use of the Gore Thoracoabdominal Multibranch Endoprosthesis for exclusion of an extent III thoracoabdominal aneurysm in the setting of degeneration proximal to a previously placed fenestrated device.